Cellulose citrate: a convenient and reusable bio-adsorbent for effective removal of methylene blue dye from artificially contaminated water. Issue 54 (22nd October 2021) - Olivito, Fabrizio; Algieri, Vincenzo; Jiritano, Antonio; Tallarida, Matteo Antonio; Tursi, Antonio; Costanzo, Paola; Maiuolo, Loredana; De Nino, Antonio
Abstract : In the present work, we proved the efficacy of cellulose citrate to remove methylene blue (MB) from artificially contaminated water. Abstract : In the present work, we proved the efficacy of cellulose citrate to remove methylene blue (MB) from artificially contaminated water. MB is a widely used dye, but because of its chemical aromatic structure, it is significantly stable with quite slow biodegradation, causing consequent serious health problems for people and significant environmental pollution. Cellulose citrate, the bio-adsorbent proposed and studied by us to remediate water polluted by MB, is produced by a green, cheap and fast procedure that makes use of two abundant natural products, cellulose and citric acid. The average of two citrate groups for each glucose unit of cellulose chains allows this material to have many carboxylic groups available for interaction with the cationic dye. The characterization was carried out through FT-IR, SEM, specific surface area, pore structure parameters and zeta potential. The negative value of the zeta potential at neutral pH is consistent with the affinity of this material for the adsorption of cationic compounds like MB. The activity of the adsorbent at different times, temperatures, pH and concentrations was investigated. The process followed monolayer adsorption typical of the Langmuir model, with a maximum adsorption capacity of 96.2 mg g −1, while for the kinetic studies the process followed a pseudo-second order model. The highest levels of adsorption were reported using solutions of dye with concentrations under 100 mg L −1 . The adsorbent can be regenerated several times without a significant loss in the adsorption capacity, and it is not strongly affected by temperature and pH, giving rise to a simple and eco-sustainable procedure for water remediation. Therefore, we conclude that cellulose citrate can be considered as a promising bio-adsorbent for the removal of MB and other cationic pollutants from the environment.